2015
DOI: 10.1038/jhh.2015.106
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability in controlled and uncontrolled blood pressure and its association with left ventricular hypertrophy and diastolic function

Abstract: High systolic blood pressure (SBP) variability has been associated with higher risk for target-organ damage. In a cross-sectional study done in a tertiary outpatient hypertension clinic, we compared short-term SBP variability among controlled and uncontrolled hypertensive patients and evaluated the association between higher levels of SBP variability and diastolic function and left ventricular hypertrophy (LVH). Patients were evaluated by 24-h ambulatory blood pressure monitoring and transthoracic Doppler echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Unfortunately, this hypothesis cannot be tested, as this accurate diagnostic information is not available for the study population. Nevertheless, in a population-based cohort and a patient-based cohort, it has been shown that there was no association between short-term blood pressure variability and subclinical target organ damage [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this hypothesis cannot be tested, as this accurate diagnostic information is not available for the study population. Nevertheless, in a population-based cohort and a patient-based cohort, it has been shown that there was no association between short-term blood pressure variability and subclinical target organ damage [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…These observations are identified in Figure 2. [23] in Brazil with an average age of 58 years. These age variations can be related to different study populations.…”
Section:  Epidemiological Datamentioning
confidence: 99%
“…Accumulating evidence has also shown that BPV observed during 24 h ABPM was also associated with an increased risk of target organ damage and early atherosclerosis in a manner which was independent of mean BP levels. 5 , 6 Several general population-based studies have reported that measures of 24 h BPV could serve as an independent predictor for CV events and all-cause mortality. 7 , 8 More recently, an increasing body of evidence has shown that increased BPV can predict CV events and all-cause mortality in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%